Security Implications and Risk Management in Low-Code and RPA Deployments (Journal of Science & Technology, 2022)
As organizations increasingly embrace digital transformation through the adoption of Low-Code Development and Robotic Process Automation (RPA), the integration of these technologies raises critical considerations regarding security and risk management. This study conducts an in-depth exploration of the security implications associated with the deployment of Low-Code and RPA solutions, aiming to provide a comprehensive understanding of the potential risks and effective risk management strategies. The research investigates the unique security challenges posed by Low-Code and RPA deployments, considering factors such as data privacy, application vulnerabilities, and the potential impact on overall IT infrastructure.